The Critical Success Factors Towards Homestay Development in Penang - Azmi, Azila; Abdullah, Azrul; Kamal, Saiful Bahri Mohd; Isa, Norshamshina Mat; Sirait, Ningrum Natasya; Purba, M Hadyan Yunhas (Journal of Ecohumanism, 2024)
Since its introduction in 1988, the Homestay Programme in Malaysia has become an iconic rural tourism product. Tourists pay a reasonable price to stay with a host family and experience daily life alongside the local community. The pandemic outbreak in February 2020 severely impacted the tourism industry, causing many homestays to cease operations. In the post-pandemic period, the tourism industry, including homestays, is striving to regain momentum. Studies have been conducted to identify critical success factors influencing homestays' success. This study focuses on identifying these factors for homestays in Penang, Malaysia, considering perspectives from tourists, government agencies, institutions, industry players, and the community. A semi-structured interview and thematic analysis were used to process data collected from eleven informants with varying levels of involvement in homestays, ranging from those directly engaged in their development to those with little or no experience in visiting them. The interviews were conducted mainly in Bahasa Melayu, with the input translated into English. The data was then classified into several themes for further discussion.